Transient Thermo Elastohydrodynamic Lubrication of Asymmetric Polymer Planetary Gear with Addendum Modification - Mingyu Zuo; Youqiang Wang; Guangxiao Jian; Yu Hu; Jun Mo; Yuxin Fang (Jixie chuandong)
In order to investigate the thermo elastohydrodynamic lubrication characteristics of internal meshing asymmetrical gears with addendum modification， the transient thermo elastohydrodynamic lubrication of asymmetrical polymer gears with addendum modification is analyzed by the multi-grid method. The elastohydrodynamic lubrication characteristics of modified gears with different transmission types are compared. The effects of different distribution forms of modification coefficients and tooth profile modification on the transient elastohydrodynamic lubrication of asymmetrical polymer gears under internal meshing are analyzed. The results show that asymmetrical tooth profile can improve the lubrication performance of the gears with addendum modification， and the positive transmission gear has the best lubrication performance. The larger modification coefficient of the inner gear is conducive to the thermo elastohydrodynamic lubrication performance. The moderate tooth profile modification can improve the lubrication performance of the asymmetric gears with addendum modification.